THE INFLUENCE OF ISO 9001:2008 CERTIFICATION TO PROFITABILITY OF FOOD AND BEVERAGE MANUFACTURING COMPANIES LISTED ON INDONESIA STOCK EXCHANGE - Soewignyo, Tonny (JBE (Journal of Business and Economics); Volume 13 No.2, 2014 JBE UNKLAB, 2014)
The purpose of this study was to find answers to the pros and cons regarding the effect of ISO 9001:2008 certification on manufacturing companies listed on Indonesian Stock Exchange, more specifically to compare the profitability of certified companies and non-certified companies using Net Profit Margin (NPM) and Return on Equity (ROE). The study used descriptive and causal research method s which also proved using dummy variable whether the certification of ISO 9001:2008 has a significant positive influence on the profitability of the companies . In addition, data on financial statement was obtained through Indonesian Stock Exchange (IDX) directory between years 2011-2013. Out of 16 food and beverage companies listed in IDX directory, 14 companies met the criteria of the sample, in which nine companies are with ISO 9001:2008 certification and five companies without. Furthermore, normality test was done to ensure the data is normally distributed. It was found that profitability—NPM and ROE—of the certified companies is superior compared to the non-certified companies although no significant difference was found. ISO 9001:2008 was found to have a significant positive influence on ROE, whereas non-certified companies showed no significant influence on ROE. Both groups showed no significant influence on the results of the NPM. ISO 9001:2008 for the moment does not promise benefits to the company unless the need for renewal in eight basic approach to quality management.